2006
DOI: 10.1080/02533839.2006.9671208
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of piled raft foundations

Abstract: This paper presents raft-pile-soil interaction for a vertically loaded flexible piled raft on layered subsoil using a two-dimensional finite difference numerical tool. The subsoil is modeled as a linear elastic material and the raft is modeled as a beam structure under plane strain. In addition, the piles are simulated by a series of pile elements considering the pile/soil interface behavior. In the simulations, the required input parameters of soil, pile and interface are determined by back analyses of pile l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…An approximate analysis for piled raft foundations for the vertical load was carried out by Ta and Small [8]. It is observed that most of the recent literatures [9][10][11][12][13][14][15] concentrated on the study of piled raft foundations under vertical loads only. Chaudhary [16] investigated the effectiveness of pile foundation in reducing 2 ISRN Civil Engineering settlement by comparing the results of piled raft foundation and the raft foundation alone.…”
Section: Background Of the Problemmentioning
confidence: 99%
“…An approximate analysis for piled raft foundations for the vertical load was carried out by Ta and Small [8]. It is observed that most of the recent literatures [9][10][11][12][13][14][15] concentrated on the study of piled raft foundations under vertical loads only. Chaudhary [16] investigated the effectiveness of pile foundation in reducing 2 ISRN Civil Engineering settlement by comparing the results of piled raft foundation and the raft foundation alone.…”
Section: Background Of the Problemmentioning
confidence: 99%
“…Finite element method was used to predict the response of piled raft foundation by Reul et al (2003Reul et al ( , 2004, Reul (2004) [20][21][22][23][24][25][26][27][28][29][30]. In addition, the application of centrifuges to model the response of piled raft foundation was also conducted by Horikoshi et al (1996Horikoshi et al ( , 1998, Vincenzo Fioravante (2008), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, many researchers have studied piled raft foundation systems. It has been reported that by increasing the pile length, pile diameter, aspect ratio, number of piles, and raft foundation thickness, the overall performance of piled raft foundations improves considerably (e.g., El-Garhy et al, 2013;Lin and Feng, 2006;Mali and Sing, 2020;Sinha and Hanna, 2017;Vu et al, 2014;Xie and Chi, 2020).…”
Section: Introductionmentioning
confidence: 99%